2009
DOI: 10.1111/j.1547-5069.2009.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Management Workforce in the United States

Abstract: To develop and deploy CCMs better matched to societal healthcare needs, characteristics of CCMs should be precisely understood. Managing the CM workforce is expected to be critical because of a shortage of RN workers and aging-of-the-workforce issues in the US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 9 publications
0
27
0
1
Order By: Relevance
“…Only one study under review (Huber et al 2003) was guided by a theoretical framework. Although CM has been well developed as a model of care delivery, the lack of a comprehensive theoretical model for CM is a real weakness because theoretical frameworks are valuable guides for research questions and design (Park & Huber 2009). Future studies also will need to develop theoretical frameworks that are able to view CM and other related concepts comprehensively and deliver value-based care to clients.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study under review (Huber et al 2003) was guided by a theoretical framework. Although CM has been well developed as a model of care delivery, the lack of a comprehensive theoretical model for CM is a real weakness because theoretical frameworks are valuable guides for research questions and design (Park & Huber 2009). Future studies also will need to develop theoretical frameworks that are able to view CM and other related concepts comprehensively and deliver value-based care to clients.…”
Section: Discussionmentioning
confidence: 99%
“…Case managers comprise a multi-disciplinary workforce and have diverse academic educational backgrounds and work environments. Some of the major professions from which case managers are drawn are nursing and social work [19], with Registered Nurses (RNs) comprising the majority of case managers in the United States[20]. HIV case managers coordinate resources and referrals to community-based social services and medical care in order to facilitate continuity of care for PLWH [21].…”
Section: Methodsmentioning
confidence: 99%
“…In developed countries such as the United States, Canada and the United Kingdom, case management has been reported as an effective care‐coordination strategy for chronic illnesses (Joo ; Park & Huber ; Park & Kim ; You et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries such as the United States, Canada and the United Kingdom, case management has been reported as an effective care-coordination strategy for chronic illnesses (Joo 2014;Park & Huber 2009;Park & Kim 2008;You et al 2013). For instance, systematic reviews have shown that case management resulted in statistically significant reductions in hospital utilization, including days in hospital, and in increased quality of and satisfaction with care (Huntley et al 2016;Joo & Liu 2017;You et al 2013).…”
Section: Introductionmentioning
confidence: 99%